Industry in seaports in Poland - Tadeusz Bocheński (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2020)
The study aims to classify port cities in Poland in terms of the development of their industrial functions and those in their immediate surroundings. Industrial plants currently operating in the vicinity of seaports were identified in the area where the port and its industrial districts have developed. Data on the volume of transhipments in individual ports, the number of manufacturing entities in gminas, including ports themselves, and on employment in industry in powiats where seaports are located, were used. The research includes both the industry directly related to the maritime economy, including shipbuilding and fish processing, as well as industrial enterprises located there for economic reasons following classical location theories. Seaports in Poland, due to the level of industrial development, can be divided into four groups: with a developed and diverse industry (Gdańsk and Szczecin), with one sector dominating (Gdynia, Police, Elbląg), with a small shipbuilding industry and factories operating for the needs of fisheries (Świnoujście, Kołobrzeg, Władysławowo, Ustka, Łeba), without any developed industry (others).